mTORC1 Dependent Regulation of REDD1 Protein Stability - Tan, Chia Yee (Public Library of Science, 2013)
REDD1 is known to be transcriptionally upregulated in hypoxia. During hypoxic stress, REDD1 plays an important role as a mediator of mTORC1 inhibition. REDD1 is also subject to highly dynamic transcriptional regulation in response to a variety of other stress signals. In addition, the REDD1 protein is highly unstable. However, it is currently not well understood how REDD1 protein stability is regulated. In this study, we discovered that mTORC1 regulates REDD1 protein stability in a 26S proteasome dependent manner. Inhibition of mTORC1 resulted in reduced REDD1 protein stability and a consequent decrease in REDD1 expression. Conversely, activation of the mTORC1 pathway increases REDD1 protein levels. We show that REDD1 degradation is not regulated by HUWE1, Cul4a or other Cullin E3 ubiquitin ligases. Our study shows that mTORC1 increases REDD1 protein stability and reveals a novel mTORC1-REDD1 feedback loop. This feedback mechanism may limit the inhibitory action of REDD1 on mTORC1.